2015
DOI: 10.1016/j.joco.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quality of life between myopic patients with spectacles and contact lenses, and patients who have undergone refractive surgery

Abstract: PurposeThe present study aims at investigating and comparing the vision-related quality of life of myopic persons who wear spectacles or contact lenses with those who have undergone refractive surgery. It also compares the vision-related quality of life of these two groups with that of emmetropes.MethodIn this study, the questionnaire of evaluation instrument of refractive error in quality of life (NEI/RQL-42) was used to compare the quality of life between 154 myopic patients with spectacles and contact lense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…To buttress this, studies have shown that refractive error patients on spectacle correction have a lower quality of life compared to those on contact lenses and those who have undergone refractive surgery. The major factor accounting for the reduced quality of life among those on spectacles is the 'inconvenience of wearing spectacles' [31,32]. This is especially important as trends in patient care have shifted towards caring for the overall person not just alleviation of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…To buttress this, studies have shown that refractive error patients on spectacle correction have a lower quality of life compared to those on contact lenses and those who have undergone refractive surgery. The major factor accounting for the reduced quality of life among those on spectacles is the 'inconvenience of wearing spectacles' [31,32]. This is especially important as trends in patient care have shifted towards caring for the overall person not just alleviation of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the QIRC was criticized to be multidimensional and hence was split into 2 unidimensional scales (functional and emotional outcomes). 2,45 Meanwhile, the QoV has been criticized for suboptimal targeting and differential item functioning, 46 whereas the NAVQ is limited by suboptimal item-fit statistics and targeting. 2…”
Section: Questionnaires For Patient-reported Outcome Measuresmentioning
confidence: 99%
“…Some studies compared this questionnaire in patients who use contact lenses, spectacles and refractive surgery and found some differences, but these data were difficult to compare with our results since the population studied was different. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%